Mexiletine rescues a mixed biophysical phenotype of the cardiac sodium channel arising from the SCN5A mutation, N406K, found in LQT3 patients. Issue 1 (1st January 2018) - Hu, Rou-Mu; Tester, David J.; Li, Ryan; Sun, Tianyu; Peterson, Blaise Z.; Ackerman, Michael J.; Makielski, Jonathan C.; Tan, Bi-Hua
ABSTRACT: Introduction: Individual mutations in the SCN5A -encoding cardiac sodium channel α-subunit usually cause a single cardiac arrhythmia disorder, some cause mixed biophysical or clinical phenotypes. Here we report an infant, female patient harboring a N406K mutation in SCN5A with a marked and mixed biophysical phenotype and assess pathogenic mechanisms. Methods and Results: A patient suffered from recurrent seizures during sleep and torsades de pointes with a QTc of 530 ms. Mutational analysis identified a N406K mutation in SCN5A. The mutation was engineered by site-directed mutagenesis and heterologously expressed in HEK293 cells. After 48 hours incubation with and without mexiletine, macroscopic voltage-gated sodium current ( I Na ) was measured with standard whole-cell patch clamp techniques. SCN5A-N406K elicited both a significantly decreased peak I Na and a significantly increased late I Na compared to wide-type (WT) channels. Furthermore, mexiletine both restored the decreased peak I Na of the mutant channel and inhibited the increased late I Na of the mutant channel. Conclusion: SCN5A-N406K channel displays both "gain-of-function" in late I Na and "loss-of-function" in peak I Na density contributing to a mixed biophysical phenotype. Moreover, our finding may provide the first example that mexiletine exerts a dual rescue of both "gain-of-function" and "loss-of-function" of the mutant sodium channel.